Analysis of Public Services for Users of the Social Security Administrator Agency (BPJS) - Erinaldi Erinaldi; Lili Suryani; Riniyah Sabah (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
This study examines the quality of outpatient public services for BPJS Health patients at the Regional General Hospital of Dumai City. The purpose of this research is to assess how service quality is experienced by patients and how effectively outpatient services are delivered. A qualitative descriptive approach was used, with data collected through direct observation, in-depth interviews, and documentation. Informants included outpatient service staff and BPJS patients selected purposively to represent both service providers and service users. The analysis focuses on five dimensions of service quality: physical facilities, service reliability, responsiveness, assurance, and empathy. The results indicate that outpatient services are generally perceived as adequate, particularly in terms of physical facilities, diagnostic accuracy, and staff professionalism. However, delays in registration and service processes remain a major concern, mainly due to high patient volume and administrative procedures. In addition, differences in staff communication and interpersonal attitudes lead to variations in patient experiences. Overall, the study highlights the importance of improving service responsiveness and strengthening empathetic communication to enhance patient satisfaction and the effectiveness of public hospital outpatient services.